Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Kerja terhadap Kinerja Guru - Damayani, Titin; Arafat, Yasir; Eddy, Syaiful (Journal of Innovation in Teaching and Instructional Media, 2020)
This study aimed at determining whether there is 1) an influence of the principal's leadership on the performance of the teachers; 2) an influence of work motivation on the performance of teachers; 3) an influence of the principal's leadership and work motivation together on the performance of the teachers. This study used a quantitative method. The research sample consisted of 103 junior high school teachers in Sungai Lilin. The data were collected using questionnaire. Data analysis techniques used 1) descriptive quantitative analysis techniques; and 2) multiple regression. The results of the study state that 1) there was a significant influence between the leadership of the principal on the performance of the teachers; 2) there was a significant influence between work motivation on the performance of teachers; 3) there was a significant influence jointly between the leadership of the principal and work motivation on the performance of the teachers.